Graphene: Complementing Graphenes: 1D Interplanar Charge Transport in Polymeric Graphitic Carbon Nitrides (Adv. Mater. 48/2015). (December 2015) - Merschjann, Christoph; Tschierlei, Stefanie; Tyborski, Tobias; Kailasam, Kamalakannan; Orthmann, Steven; Hollmann, Dirk; Schedel‐Niedrig, Thomas; Thomas, Arne; Lochbrunner, Stefan
Abstract : On page 7993, C. Merschjann and co‐workers use transient photoluminescence to study charge transport in semiconducting polymeric graphitic carbon nitrides, finding that electrons and holes show surprisingly high mobilities. Furthermore, they move predominantly along channels perpendicular to the graphitic sheet structure. Thus, carbon nitrides effectively complement 2D materials like graphene, opening potential routes for novel organic electronic devices.